Optimization of a cooling system in data centers - Ali, Maisarah; Jusoff, Kamaruzzaman; Romadhan, Rahmat; Abakr, Yousifabdalla (Kaerntner Botanikzentrum, 2012)
Rapid growth in the information and communication technology has increased the demand for equipment in data centers. However, this is not followed by the expansion of space. The increase in high density data center equipment gives impact to the increase heat dissipation. Cooling system in a data center consumes the highest power utilization after the IT equipment. The optimization of performance of the cooling system will give significant benefit for energy efficiency. The objective of the study is to show the importance of numerical simulation in order to find the optimum arrangement of racks in data centers. Optimization could be achieved by the arrangement of racks position and improvement in the cooling system and airflow management. Models and simulation of Computational Fluid Dynamics (CFD) are developed for the room and equipment of data center where theeffect to temperature profiles will be observed. A case study of data center design in Kuala Lumpur with 30 racks of equipment and combination of raised floor cooling and spot cooling was carried out. Results of CFD simulation show the problems arose in data center cooling and improvement was suggested to improve the distribution of cooling and reduction of hot spots.